Analisis Pemanfaatan Limbah Padat Pabrik Kelapa Sawit menjadi Bahan Bakar PLTU (Studi Kasus : PT. Agro Mitra Madani Kabupaten Tanjung Jabung Barat) - G M Saragih; Hadrah Hadrah; Rahmad Fatulloh (Universitas Batanghari Jambi, 2020)
Palm oil mills as raw materials for domestic industry and are the main export commodities can potentially produce solid waste that needs to be treated in order to avoid environmental pollution. The best treatment is if the waste is used as an energy source. The study was conducted to determine the energy produced from the utilization of palm shell and palm fiber solid waste carried out at PT Agro Mitra Madani, Tanjung Jabung Barat District, Jambi Province. This study aims to determine the number of shells and fibers produced and used as materials for boilers, analysis of electrical energy from solid waste of palm shells and fibers, and mass balance analysis from the burning of shells and fibers. The composition of the boiler is 25% shell and 75% fiber. The energy used by factories from shell and fiber solid waste is the amount of energy produced multiplied by the length of shift time, which is 7 hours. The plant's electricity demand is 4,900 kWh and the amount of electricity produced from the fibers and shells as boiler fuel is 8,253 kWh. Based on the calculation results, it can be seen that the excess power for 7 hours is 3,353 kWh and the amount of residue is 654 kg / shift. These results indicate that the utilization of oil palm shells and fiber into electrical energy is feasible.